The role of predictive and preview effects in Mongolian reading: evidence from eye movements - Lu, Zhang; Ri, Na; Jingxin, Wang (Frontiers in Psychology, 2024)
The research on contextual predictability in reading has been thoroughly investigated in the context of horizontal text comprehension. However, the performance of contextual predictive effects in Mongolian vertical reading remains unknown. Recently, there has been further research discussing how contextual predictive effects may be influenced by parafoveal processing. Thus, employing a boundary paradigm, we conducted an eye-tracking study aimed at exploring contextual predictability and preview effects in Mongolian reading. Our study found significant main effects of predictability and previewing in terms of temporal indicators, but not in terms of skipping rates, nor did we find an interaction between the two. We speculate that the unique reading orientation and writing features of Mongolian, compared to phonetic scripts read horizontally, diminish the parafoveal processing of preview information, resulting in lower skipping rates in Mongolian reading.